Effect of Bran Powder on the Quality and Microstructure of Whole Grain Breads - WEI Yi-min (Liang you shipin ke-ji)
Wheat bran is an important source of dietary fiber for humans. Compared to regular bread, whole grain bread differs in shape, texture, and taste，which affects consumer experience. Improving the taste and texture of whole wheat bread is the main challenge in increasing the consumption of whole wheat products. In this study, bread flour produced from strong gluten wheat varieties in domestic was used as raw material. By adding different types and quantities of bran powder and utilizing a C-Cell image analyzer, the research analyzed the impact of bran fiber on the microstructure of bread. It examined the changes in the bread's microstructure, including its shape and internal structure. The results showed that bran fiber primarily reduced bread volume by decreasing the thickness of bread cell walls, the diameter of air pockets, the number or area of air pockets, and the brightness of the bread. It also affected the sensory characteristics of the bread. Improving the structure and mouthfeel of whole wheat bread is an effective way to increase consumer satisfaction with whole wheat bread products.